Neurophysiological follow-up in peripheral nerves grafts - Portillo, Roberto (2003)
OBJECTIVE: Neurophysiologic follow-up of 10 patients with peripheral nerves grafts. SETTING: Clinical Neurophysiology Unit, Guillermo Almenara Irigoyen National Hospital, EsSalud. MATERIAL AND METHODS: Ten 6 to 39 year-old patients with nerve grafts for peripheral nerve wounds in upper limbs were studied. Neurophysiologic control by electromyography, motor and sensitive speed nerve conduction was done periodically. RESULTS: An excellent evolution of the 10 peripheral nerve graft cases was demonstrated by the electrophysiology follow up, most of them with early recuperation of the motor nerve conduction and sensitive recuperation, as in cases of cubital lesion (cases 4, 7 and 8) and cubital and median lesions (case 10). Clinical recovery showed correlation with neurovegetative, motor and sensitive changes. CONCLUSIONS: Electrophysiology plays an important role in the evaluation of post-surgery peripheral nerve grafts. The time of clinical and electrophysiolgical recuperation varies from 1 to 2 years or more. Surprisingly, clinical recovery is not always related to electrophysiological findings; in some cases recovery is acceptable and in others the electrophysiological recuperation is slower than clinical recovery.